2004
DOI: 10.1017/s1367943004001234
|View full text |Cite
|
Sign up to set email alerts
|

A second outbreak of rabies in African wild dogs (Lycaon pictus) in Madikwe Game Reserve, South Africa, demonstrating the efficacy of vaccination against natural rabies challenge

Abstract: An outbreak of rabies in a pack of endangered wild dogs (Lycaon pictus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 21 publications
1
45
1
Order By: Relevance
“…Catastrophic events such as those caused by disease or human persecution can have significant impacts on tiny wild dog populations (Ginsberg et al, 1995;Ginsberg & Woodroffe, 1997;Hofmeyr et al, 2000;Hofmeyr, Hofmeyr, Nel & Bingham, 2004). Although catastrophic disease outbreaks (canine distemper) led to the extinction of one subpopulation during the period covered by this study (Tswalu 2005), this represented just 3.6% and 4.9% of adults and pups in the metapopulation, respectively.…”
Section: Other Factors Influencing Survival and Population Viabilitymentioning
confidence: 86%
“…Catastrophic events such as those caused by disease or human persecution can have significant impacts on tiny wild dog populations (Ginsberg et al, 1995;Ginsberg & Woodroffe, 1997;Hofmeyr et al, 2000;Hofmeyr, Hofmeyr, Nel & Bingham, 2004). Although catastrophic disease outbreaks (canine distemper) led to the extinction of one subpopulation during the period covered by this study (Tswalu 2005), this represented just 3.6% and 4.9% of adults and pups in the metapopulation, respectively.…”
Section: Other Factors Influencing Survival and Population Viabilitymentioning
confidence: 86%
“…Additionally, it is of interest that the sole surviving pack member identified in mid-2007 was one of only two pack members that had been previously vaccinated against rabies. However, the vaccine was administered six years earlier, and the individual never received a booster vaccine; the efficacy of a single rabies vaccination in preventing mortality after exposure to the virus has been variable in previous reports [32,33,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Hofmeyr et al [33] reported that although rabies vaccination can have a beneficial impact in the face of a disease epidemic, multiple doses may be needed to ensure protection. Vial et al [50] advocate that rabies vaccination of a "core" population of 30-40% of wild dogs in small populations every 1-2 years would theoretically be effective at controlling rabies and thus ensuring wild dog persistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"NP" or "NPs" denote a National Park and National Parks, respectively and "GR" denotes a Game Reserve. 1978, 1989, 19902002 (Madikwe) Rabies have thwarted attempts to reintroduce endangered wild dogs in Etosha National Park, has resulted in two successive outbreaks in wild dog packs in Madikwe, South Africa (Hofmeyr et al, 2000 andHofmeyr et al, 2004), and has been identified as the cause of the loss of five packs in Botswana (Woodroffe et al, 2004 1955,1969,1970,[1974][1975][1976] …”
Section: Appendixmentioning
confidence: 99%